Pay it forward - Leder, Mimi, 1952-; Dixon, Leslie; Spacey, Kevin; Hunt, Helen; Osment, Haley Joel, 1988-; Hyde, Catherine Ryan.; Copyright Collection (Library of Congress) (United States : Warner Bros., 2000)
Young Trevor McKinney, troubled by his mother's alcoholism and fears of his abusive but absent father, is caught up by an intriguing assignment from his new social studies teacher, Mr. Simonet. The asignment, think of something to change the world and put it into action. Trevor's efforts to make good on his idea bring a revolution not only in the lives of himself, his mother and his physically and emotionally scarred teacher, but in those of an ever-widening circle of people completely unknown to him.
Copyright: unknown.
An unattached trailer included with this feature: Proof of life (CEA 1110).
Summary taken partly from the Internet Movie Database, 8-9-2001.
An unattached trailer for the feature Joe versus the volcano received along with this feature for copyright deposit.
Based on the novel by Catherine Ryan Hyde.
Sources used: Internet Movie Database, 8-9-2001; Variety, 10-9-2000; copyright data sheet; copyright database.
Keywords: Alcoholism -- Drama; Families -- Drama; Interpersonal relations -- Drama; Family -- Feature; Social problem films; Fiction films; Film adaptations